Neuromuscular fatigability during repeated sprints assessed with an innovative cycle ergometer - Di Domenico, H.; Beaume, J. B.; Peyrard, A.; Samozino, P.; Bowen, M.; Hintzy, F.; Millet, G. P.; Hayes, M.; Lapole, T.; Rupp, T. (European Journal of Applied Physiology, 2022)
Purpose Repeated sprint ability is an integral component of team sports. This study aimed to evaluate fatigability development and its aetiology during and immediately after a cycle repeated sprint exercise performed until a given fatigability threshold.